CITRA TUBUH DAN KEPUASAN PERNIKAHAN ISTRI PADA USIA DEWASA TENGAH - Tiara, Monica; Qudsyi, Hazhira (Psychopolytan (Jurnal Psikologi), 2018)
This study aims to test relationship between body image and marital satisfaction among wife. Respondents of this study were 48 women lived in Bekasi. Measurement of marital satisfaction was done by using ENRICH Marital Satisfaction Scale from Fower and Olson (1993). This scale has 14 items with reliability coefficient of Cronbach Alpha 0.864. Meanwhile, body image in this research was measured using Body Shape Questionnaire (BSQ) from Gupta (2011), with reliability coefficient of Cronbach Alpha 0.939. Result of correlation analysis showed that there were significant correlation between body image and marital satisfaction among wife in middle adulthood (r=0.350, p=0.0008, r2=0.122).   Keywords:  body image, marital satisfaction, wife, middle adulthood